THE LEARNING MANAGEMENT SYSTEM APPLICATION CONTRIBUTION ON TECHNOLOGY CYBER USAGE TOWARDS COMPLEXITY OF EDUCATION WITHIN MANAGEMENT CLASS ACTION IN 21st CENTURY - Velma Alicia Ali (Dialectical Literature and Educational Journal, 2021)
This study investigates a number of theories about the sophistication of cyber technology-based classroom management through the application of a learning management system, especially the results of previous research through literature review as well as the thoughts and experiences of educational practitioners, technologists, academics, and theorists both related to education. with regard to education. The purpose of this research is to photograph the problems of a number of higher and secondary education institutions in Indonesia regarding the urgency of cyber technology to support the effectiveness and efficiency of learning models in the 21st Century. By identifying the obvious problems, a model for implementing classroom action management is sought, especially the stages or prerequisites. that must be met for the implementation of 21st Century Education. Educational institutions are constantly developing curricula according to the paradigm shifts of the global community both in terms of science and technology to operational matters, namely educational processes and management supported by Information and Communication Technology. The research method using descriptive-qualitative begins with a literature study, in-depth interviews with the respondents involved using the snowball sampling technique. The results of the literature study and interviews are used as an inviting paper to be discussed in a focus group discussion (FGD) forum to conduct needs assessments and equalize perceptions (intersubjectivity) for academics, theorists, students, scientists, and education staff. Thus, comprehensive conclusions and recommendations for optimizing the implementation of Education in 21st Century.